GDP growth as a bank loan quality determinant - Joanna Rachuba (Journal of Banking and Financial Economics)
Past financial crises and recessions have revealed the importance of the economy’s condition for the loan quality. Macroeconomic determinants of the non-performing loans have been attracting considerable attention in recent years. The aim of this paper is to organize and summarize studies examining the role of GDP growth and its impact on bank loan quality. This approach reveals the research problem which is to specify if there exists a statistically significant relationship between economic growth and the level of non-performing loans. It is equally important to determine the direction of this link. By appealing to common knowledge, the research hypothesis states that an increase in economic activity results in improving loan quality. To verify the hypothesis, the analysis of the relevant literature and the methods of verbal as well as tabular description have been applied. Empirical results on the link between the macroeconomic environment and the level of non-performing loans appear to be quite conclusive. It has been found that an economic expansion generally improves the loan quality. This broadly proven relationship is in line with many studies which confirm the borrowers’ increased willingness to repay debts in a favourable economic environment. Far less frequently, the macroeconomic activity leads to future bank losses. Additionally, some studies do not provide any statistically significant effect of GDP growth on the loan quality.